Legal Resources of Historical and Cultural Heritage: Presentation in Library Collections and Their Popularization - POLOVYNCHAK, Y. M.; BONDARENKO, V. I.; MATVIICHUK, L. O.; STRUNHAR, V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2022)
Objective: to substantiate the significance of historical documents of legal concern in digital library resources of historical and cultural heritage as an important component of cultural memory; to generalize modern approaches to improving the popularization of these library resources in the information space. The methods of systematic analysis of library databases of historical and cultural heritage have been used in the research, in particular, the V. I. Vernadsky National Library (Ukraine), World Digital Library, Europeana, Gallica, Bavarian State Library, etc. Results. The monuments of law as a component of historical and cultural heritage, which need to be popularized in the information space, given the scientific, educational, and ideological significance, have been studied. Conclusions. The resources of monuments of law testify to the longevity of historical development, the heredity of legal culture, and the involvement of Ukrainian political and legal thought in the European context. Digitization of such documents and their inclusion in digital collections expands user access to monuments of law and intensifies their circulation in the cultural information space. Effective work directions on the popularization of digital sources of historical and cultural heritage according to the results of the analysis of foreign experience are the use of mobile technologies and the representation of resources in social media.